Effectivitas of Pitcher Fertigation System on Bushes Pepper Crops - Hemantoro .; B. I. Setiawan; S. Hardjoamidjojo; M.H. Bintoro (PERTETA, 2003)
The successful application of pither irrigation system has motivated to investigate the pitcher as a fertigation system. The experiment was conducted at Leuwikopo Experiment Station, Agricultural Engineering Departement, Bogor Agricultural University. The main objective of this study is to study the effectiveness of pitcher fertigation system on bushes pepper crops. The result shows that the pitcher wall is capable to release NPK solution. Diffusion rate of fertilizer solution was measured as affected by the concentration inside and outside of the pitcher. The soil moisture distribution in the soil is sufficient to transport the solution available for crops development. Concentration of Phosphate (P) and Potassium (K) decrease laterally and the Nitrogen (N) tends to accumulate homogeneosly in moist part around the pitcher.